Analyzing the Method of English Department Students in Translating English Text at Sintuwu Maroso University - Sitti Fitriawati Mamudi (Sintuwu Maroso Journal of English Teaching, 2019)
The objective of the research is to find out the method of sixth semester students of English Faculty in translating English text at Sintuwu Maroso University. The writer apply the descriptive qualitative method in process of analyzing data. The writer use descriptive text entitle The Eiffel Tower as object of the research. This object is consist of 259 words and 15 sentences which translated by the sixth semester students of English Department of Sintuwu Maroso University that consist of 29 (participated is 15) student. The result of students’ translating show that the students use literal translation have total percentage 6,66%. Faithful translation with total percentage 12,44%. Semantic translation with total percentage 55,55%. Word for word translation with total percentage 4,44%. The last is free translation used with total percentage 20,88%. The highest percentage of translation method that used by students is semantic translation